INFLUENCE OF TUNGSTEN AND MOLYBDENUM ON Н2О2 ACCUMULATION IN N.BENTHAMIANA PLANT - Beisekova , M.; Zhangazin , S.; Kurmanbayeva , A.; Masalimov , Zh.; Akbassova , A. (Eurasian Journal of Applied Biotechnology, 2022)
The problem of soil pollution with heavy metals is one of the main factors hindering the development of agriculture in Kazakhstan. Soil pollution with heavy metals, especially tungsten, leads to a deterioration in plant growth and development, the formation of active oxygen radicals, and oxidative stress. In plants, tungsten (W) acts as an inhibitor of molybdoenzymes, replacing molybdenum (Mo) in the Mo-cofactor structure. At the same time, Mo itself at high concentrations also negatively affects plant cells. When exposed to tungsten and molybdenum, reactive oxygen species (ROS) accumulate excessively in the plant. When the test plant N. benthamiana is exposed to molybdenum, the accumulation of Н2О2 is sharply reduced compared to the control plant, and in plants treated with a solution of tungsten, the accumulation of Н2О2 is increased by 2 times. The accumulation of Н2О2 in plants treated with a combined solution of molybdenum and tungsten was higher compared to the control plant. An interesting result is an increase in the accumulation of Н2О2 by 3.5 times when exposed to tungsten compared to molybdenum.